2011
DOI: 10.1258/acb.2010.010214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome indicators, disease prevalence and test request variability in primary care

Abstract: Aim: To describe differences in biochemistry test request rates (adjusted for practice size) between general practices and to investigate whether differences in HbA 1c and thyroid function test request rates are related either to the practice prevalence of hypothyroidism and diabetes or to Quality and Outcome Framework (QOF) scores. Methods: Information on test request rates, prevalence of diabetes and hypothyroidism, and QOF data over a one-year period were obtained from 58 practices covering a population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
(15 reference statements)
2
14
0
1
Order By: Relevance
“…O'Kane et al . found large variations in test rates for HbA1c and thyroid functions, but no association with disease prevalence or clinical outcome measures . Hippisley‐Cox found no association between overall referral rates and stages of breast and colorectal cancer .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…O'Kane et al . found large variations in test rates for HbA1c and thyroid functions, but no association with disease prevalence or clinical outcome measures . Hippisley‐Cox found no association between overall referral rates and stages of breast and colorectal cancer .…”
Section: Discussionmentioning
confidence: 96%
“…17 O'Kane et al found large variations in test rates for HbA1c and thyroid functions, but no association with disease prevalence or clinical outcome measures. 18 Hippisley-Cox found no association between overall referral rates and stages of breast and colorectal cancer. 19 A recent study by Shawihdi et al found an association between low gastroscopy referral rate and poorer outcomes of oesophago-gastric cancer regarding emergency admission, major surgery, and mortality.…”
Section: Comparison With Existing Literaturementioning
confidence: 95%
“…Turchin et al 97 also showed that frequent HbA1c testing in patients with diabetes resulted in shorter time to target HbA1c level, independently of confounders such as initial HbA1c level, treatment-associated factors, frequency of encounters with healthcare professionals and patient demographics. O'Kane et al 24 showed that there was no correlation between the number of HbA1c tests performed and the proportion of patients in general practises with HbA1c of <58 mmol/mol (<7.5%), raising questions over the impact of testing frequency on management. Such data providing clear links between appropriateness of testing and clinical outcomes are needed for demand management interventions if they are to be widely accepted by clinical staff.…”
Section: Does It Make a Difference? Assessing The Impact Of Interventmentioning
confidence: 99%
“…It is only recently that studies have explored the relationship between testing rate and outcome. O'Kane et al 64 have challenged the concept that the rate of testing is related to outcomes. In contrast, a different study, using glycated haemoglobin as an indicator, has shown that more tests are done in patients with complications, suggesting that the greater testing rate reflected greater clinical activity and was probably appropriate.…”
Section: Efficientmentioning
confidence: 99%